FEATURES OF IMPROVING THE TAX ADMINISTRATION OF MAJOR TAXPAYERS (Academicia Globe: Inderscience Research, 2023)
Ensuring the necessary level of tax and other compulsory payment collection in the Republic of Uzbekistan, There is a special emphasis on improving the provision of service-technical services based on cooperation in organizing large-scale taxpayer activities, implementing taxpayer tax administration, and fulfilling tax obligations. On December 28, 2018, the President of the Republic of Uzbekistan, Sh.M. Miriam, In his Address to the Assembly, he said: "It is not tax evasion, it should be interested in paying it on time. The new edition of the Solidarity Code should include encouraging honest, honest taxpayers who are the pillars of the country's development and punishing those who operate in secret. By reducing the tax burden, it is necessary to introduce the same fair tax regime for all, gradually abolishing tax credits." 1